2012
DOI: 10.1186/1472-6963-12-40
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with antenatal care adequacy in rural and urban contexts-results from two health and demographic surveillance sites in Vietnam

Abstract: BackgroundAntenatal Care (ANC) is universally considered important for women and children. This study aims to identify factors, demographic, social and economic, possibly associated with three ANC indicators: number of visits, timing of visits and content of services. The aim is also to compare the patterns of association of such factors between one rural and one urban context in northern Vietnam.MethodsTotally 2,132 pregnant women were followed from identification of pregnancy until birth in two Health and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
108
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(137 citation statements)
references
References 18 publications
25
108
3
1
Order By: Relevance
“…In a study published in 2012, authors reported a proportion of late ANC attenders in 30.9% of women in FilaBavi, a rural health and demographic surveillance site of Hanoi, in the north of Vietnam. The proportion was 2.8% in an urban site of Hanoi [26]. Such a higher value in the North compared to our study, which was also conducted in a rural area, can be explained by different reasons.…”
Section: Discussioncontrasting
confidence: 72%
“…In a study published in 2012, authors reported a proportion of late ANC attenders in 30.9% of women in FilaBavi, a rural health and demographic surveillance site of Hanoi, in the north of Vietnam. The proportion was 2.8% in an urban site of Hanoi [26]. Such a higher value in the North compared to our study, which was also conducted in a rural area, can be explained by different reasons.…”
Section: Discussioncontrasting
confidence: 72%
“…A study conducted with 2132 pregnant women in Ha Noi, northern Vietnam, showed that the use of antenatal care was significantly lower in rural areas compared to urban areas. This included both the quantity, number and timing of the visits and the content of the visits .…”
Section: Discussionmentioning
confidence: 99%
“…11,13 All procedures/processes provided were weighted equally. For the purpose of this study, women, who received at least seven out of the eight procedures mentioned above were considered to be receiving appropriate content, in line with the selection criteria used by previous studies.…”
Section: Methodsmentioning
confidence: 99%